Microplastic exposure induces HSP90α secretion and aggravates asthmatic airway remodeling via PI3K-Akt-mTOR pathway - Mingming Xu; Jiyuan Chen; Lin Gao; Shaoxi Cai; Hangming Dong (Ecotoxicology and Environmental Safety)
Microplastics pollution has raised a considerable awareness due to their extensive distribution in the environment. It has potential side effects on human health. Microplastics can enter the human respiratory system, then deposit in the lung, destroying the structure of the bronchus and alveoli, and causing pulmonary inflammation, mucus production, and airway hyperresponsiveness, leading to the aggravation of asthma. Nevertheless, the underlying mechanism remains elusive. There are several cytokines involved in the inflammatory response of asthma. Heat shock protein 90α(HSP90α) is one of cytokines involving in inflammation which is a member of the HSPs family. The aim of this study is to explore the mechanism by which microplastics influence the secretion of HSP90α and the progression of asthma. Initially, we found that microplastics were destroyed airway epithelial barrier, resulting in inherent dysfunction in the secretion of HSP90α. Then, microplastics were proved to activate PI3K-Akt-mTOR pathway by prompting airway epithelial cells secrete HSP90α and proliferation of airway smooth muscle cells(ASMCs), leading to airway narrowing and hypersensitivity. 1G6-D7 is a monoclonal antibody to HSP90, which can reverse the pulmonary inflammation infiltration, mucus production, and airway hyperresponsiveness(AHR). Overall, these finding suggested that microplastics elicited inflammation via the PI3K-Akt-mTOR signaling pathway and stimulated the proliferation of ASMCs. Hence, the present study unveils a novel mechanism responsible for microplastic-induced inflammation and airway hyperreactivity, establishing a basis for further research and risk evaluations of microplastics.